Ubiquitination and endocytosis of cell adhesion molecule DM-GRASP regulate its cell surface presence and affect its role for axon navigation - Thelen, Karsten; Zelina, Pavol; Pollerberg, G. Elizabeth (The journal of biological chemistry, 2008)
DM-GRASP, cell adhesion molecule of the immunoglobulin superfamily, has been shown to promote growth and navigation of axons. We here demonstrate that clustering of DM-GRASP in the plasma membrane induces its rapid internalization via dynamin- and clathrin-dependent endocytosis, which is controlled by phosphatidylinositol 3-kinase and mitogen-activated protein kinase ERK. The clustering of DM-GRASP activates ERK; the intensity and duration of ERK activation by DM-GRASP do not depend on rapid clathrin-mediated internalization of DM-GRASP. Moreover, the preference of retinal ganglion cell axons for DM-GRASP-coated micro-lanes requires clathrin-mediated endocytosis for the appropriate axonal turning reactions at substrate borders. Because the intracellular domain of DM-GRASP does not contain motifs for direct interactions with the endocytosis machinery, we performed a yeast two-hybrid screen to identify intracellular proteins mediating the uptake of DM-GRASP and isolated ubiquitin. Immunoprecipitation of DM-GRASP coexpressed with ubiquitin revealed that one or two ubiquitin(s) are attached to the intracellular domain of cell surface-resident DM-GRASP. Furthermore, elevated ubiquitination levels result in a decrease of cell surface-resident DM-GRASP as well as in the amount of total DM-GRASP. The endocytosis rate is not affected, but the delivery to multivesicular bodies is increased, indicating that DM-GRASP ubiquitination enhances its sorting into the degradation pathway. Together, our data show that ubiquitination and endocytosis of DM-GRASP in concert regulate its cell surface concentration, which is crucial for its function in axon navigation.
Gesehen am 09.05.2017